Antecedents and Consequences of Work Life Balance : A Literature review - Fisna Adhyaksa (Eduvest - Journal of Universal Studies, 2025)
The COVID-19 pandemic has caused many changes in people's lives around the world. Policies prohibiting outdoor activities have led to condition threatened, isolated, or flavor No safe to time future. In the professional world, companies need to create the right work environment so employees can achieve work-life balance. Human resource management in every company must address this challenge by developing ways to increase employee engagement as a key resource for corporate success. Balance life Work And House or Which normal called Work life Balance can have a negative impact on employee mental health if the boundaries role employee in work And family become No clear. This study aims to conduct a systematic literature review on work-life balance variables obtained from various international research publications. This study uses method Systematic Literature Review And data study using Services Analyze Search Results from Scopus